H -Supplemented Sub Modules through Non-Cosingular Modules - Tolesa DEKEBA Bekele (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The classes of H-supplemented sub modules are a very nice generalization of lifting modules which have been studied approximately recently. In this paper, we would like to address some general and specific characterizations and properties of